Formulation development and characterization of a transdermal patch containing Crinum asiaticum leaves extract - Tan Suwandecha, Papassara Changklang (Journal of Applied Pharmaceutical Science, 2023)
Crinum asiaticum Linn. is an ethnomedicinal plant used to relieve musculoskeletal pain in traditional Thai medicine. The traditional use is hot compression with C. asiaticum leaves. A transdermal patch is one of the novel routes to deliver active compounds in C. asiaticum through the skin. This study aimed to formulate and evaluate a C. asiaticum leaves extract the transdermal patch. The main compositions of the transdermal patch were hydroxypropyl methylcellulose (HPMC), polyvinyl alcohol (PVA) PEG-400, and C. asiaticum leaves extract. The transdermal patch is prepared by solvent evaporation technique. The effects of HPMC, PVA, and PEG-400 on physical properties, such as thickness, weight uniformity, and moisture absorption, were evaluated. Lycorine, the main phytochemical in C. asiaticum, was analyzed using high performance liquid chromatography. The in vitro drug release study of the patch was carried out through the Franz diffusion cell. The transdermal patch containing PVA and PEG 400 as plasticizers showed good physical properties. The drug release was over 80% in formulations containing 2% PVA and 1%–5% PEG 400. The in vitro drug release data was fitted with kinetic equations and followed Higuchi’s diffusion mechanism. In conclusion, the transdermal patch containing 2% PVA and 2% PEG 400 has achieved the targets of this study as it had good tensile strength and drug release profile.
Keywords: Transdermal patch, Crinum asiaticum, transdermal drug delivery system